Corrosion Behavior of Nickel-Titanium Arch Wires Following the Use of Different Mouthwashes: An In Vivo Study - Gonca Yıldırım; Feyza Eraydın; Didem Nalbantgil (Galenos Yayinevi, 2024)
Objective: The aim of this double-blind in vivo study was to compare the extent of corrosion on the surface of nickel-titanium (NiTi) wires in various mouthwashes. Methods: A total of 80 patients who received orthodontic treatment with as-received 0.016x0.022 inch NiTi wires were included in the study, and they were split into 4 groups. The first group used 0.05% of (225ppm Fˉ) sodium fluoride (NaF) (Colgate Plax®) containing mouthwash, 21.6% alcohol (Listerine Cool Mint®) containing mouthwash, and 0.2% clorhexidine (CHX) (Klorhex®) containing mouthwash and the control group used drinking water with melt menthol as mouthwash. After 30 days of using mouthwash, the surfaces of NiTi wires were examined with atomic force microscopy (AFM), and surface roughness values were calculated. Results: Mouthwashes containing fluoride, essential oils, and CHX created higher surface roughness on NiTi wires than the control group. The floride-containing mouthwash group showed less corrosion than the CHX group, whereas there was no difference between the essential oil group. AFM images show supportive data with the results of the clinical study. The results were assessed using a 95% confidence interval and a significance level p<0.05. Conclusion: CHX, essential oil, and floride-containing mouthwashes cause corrosion of NiTi wires. Floride-containing mouthwash can be preferred over CHX mouthwash due to its lesser corrosion effect.